Odpowiedzi

  • hels
  • Rozwiązujący
2010-03-18T16:19:27+01:00
Y= 9 - 5x
2x+3 ( 9 - 5x )=1

y=9-5x
2x + 27 -15x = 1

y=9-5x
2x -15x= 1 - 27

y=9-5x
-13x= -26//-13

y=9-5x
x=2

y=9-5 x 2
x=2

y=9-10
x=2

x=2
y=-1
2010-03-18T16:21:47+01:00
5x+y=9
2x+3y=1

y=9-5x
2x+3y=1

y=9-5x
2x+3(9-5x)=1

y=9-5x
2x+27-15x=1

y=9-5x
-13x=-26

y=9-5x
x=2

y=-1
x=2
2010-03-18T16:22:05+01:00
2x+3 ( 9 - 5x )=1

y=9-5x
2x + 27 -15x = 1

y=9-5x
2x -15x= 1 - 27

y=9-5x
-13x= -26/-13

y=9-5x
x=2

y=9-5 x 2
x=2

y=9-10
x=2
x=2
y=-1